Asuhan Keperawatan Medikal Bedah pada Tn. dengan ADHF dan Penerapan Foot Elevation 30 Derajat untuk Menurunkan Foot Edema di Ruangan CVBC Lt. 3 RSUP Prof R.D Kandou Manado - Kaani, Jimri Novrian; Muhamad Nurmansyah; Fernandez, Gratsia Victoria (Mapalus Nursing Science Journal, 2025)
Background. Acute Decompensated Heart Failure (ADHF) is acute heart failure which is defined as a rapid onset of symptoms or signs due to abnormal heart function. Heart failure is known in several terms, namely left, right, and combined or congestive heart failure, in this case patients with right heart failure are characterized by the presence of peripheral edema, ascites and increased jugular veins, in patients who experience heart disease edema caused by pump failure, edema that occurs in patients can cause discomfort, difficulty walking, The best way to reduce edema is to take advantage of the nature of the fluid that always goes to a lower place due to the influence of gravity and one of the exercises that can be given to patients with heart failure is the provision of a higher leg position of 30˚ for 3x a day, done for approximately 15-30 minutes. Objective. Describing the results of practice in the form of nursing care in ADHF patients with the provision of 30 degree elevation in reducing edema. Results : after giving foot elevation 30 degrees for 5 days the results obtained that the level of edema in the legs from the initial 4/4 dropped to 0/2 degrees, so with these results it can be concluded that giving foot elevation 30 degrees is effective in reducing the degree of edema. Conclusion : the intervention given by EBPN, namely foot elevation of 30 degrees in reducing the degree of edema, has significant results where the patient's edema drops to grade 0. Keywords: ADHF ;Edema:Foot elevation